The Role of Islamic Bonds (Sukuk) toward Indonesia Economy - Darania Anisa; Rudi Santoso (Sekolah Tinggi Ekonomi dan Bisnis Islam Lampung, 2020)
The development of Islamic bonds (sukuk) has a great potential. Islamic bonds (sukuk) is an investment instrument which can be utilized by the government to build nation economy and create public welfare. In 2019, the total value of sukuk emissions amounted IDR 48,240.40 billion with an sukuk outstanding value of IDR 30,203.50 billion from a total of 145 corporate sukuk circulating on the Islamic capital market. The role of Islamic bonds (sukuk) for the government in increasingly important, especially as an alternative source of funding for the state budget. Of course, if national development in Indonesia uses sukuk, it will be better direct debt. At least, the orientation of the issuance of state Islamic bonds (sukuk) is based on three things: 1) infrastructure development, 2) labor-intensive sectors, 3) and, optimization of potential.